THE EFFECT OF EMPATHY AND PREVIOUS EXPERIENCES ON SOCIAL ENTREPRENEUR BEHAVIOR WITH SELF-EFFICACY, OUTCOME EXPECTATIONS AND SOCIAL SUPPORT AS MEDIATOR IN JAKARTA - Sephira, Valerie; Selamat, Frangky (International Journal of Application on Economics and Business, 2023)
This study aims to empirically examine the effect of empathy and prior experience on social entrepreneurial behavior with self-efficacy, outcome expectation and perceived social support as mediator. The sampling technique used in this research is non-probability sampling using convenience sampling technique. Data collection using a google form questionnaire distributed through social media with a total of 200 respondents. Data processing in this study using SmartPLS software version 3.2.9. The sample in this study is social entrepreneur who live in Jakarta. The results of the analysis of this study are: 1) self-efficacy can positively and significantly effect on social entrepreneurial behavior, 2) outcome expectation can positively and significantly effect on social entrepreneurial behavior, 3) perceived social support can positively and significantly effect on social entrepreneurial behavior, 4) empathy can positively and significantly effect on social entrepreneurial behavior with self-efficacy, outcome expectation and perceived social support, 5) prior experience can positively and significantly effect on social entrepreneurial behavior with self-efficacy, outcome expectation and perceived social support.